2018
DOI: 10.20944/preprints201806.0110.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Insights into the Configurations of Lead(II)-Benzohydroxamic Acid Coordination Compounds in Aqueous Solution: A Combined Experimental and Computational Study

Abstract: Novel collector lead(II)-benzohydroxamic acid (Pb(II)-BHA) complexes in aqueous solution were characterized by using experimental approaches, including Ultraviolet-visible (UV-Vis) spectroscopy and electrospray ionization–mass spectrometry (ESI-MS), as well as first-principle density functional theory (DFT) calculations with consideration for solvation effects. The Job plot delineated that a single coordinated Pb(BHA)+ should be formed first, and the higher coordination number complexes can be formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Some researchers confirmed that the Pb-BHA complexes existed mainly in the form of Pb-(BHA) n = 1, 2 in solution (Han et al, 2017b; Yue et al, 2017; He et al, 2018a), in order to compare the species between Pb-BHA complexes and Pb-BHA complexes adsorbed on mineral surface, the XPS measurements were conducted. Table 1 shows the electron binding energy of the different elements of BHA and Pb-BHA complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers confirmed that the Pb-BHA complexes existed mainly in the form of Pb-(BHA) n = 1, 2 in solution (Han et al, 2017b; Yue et al, 2017; He et al, 2018a), in order to compare the species between Pb-BHA complexes and Pb-BHA complexes adsorbed on mineral surface, the XPS measurements were conducted. Table 1 shows the electron binding energy of the different elements of BHA and Pb-BHA complexes.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, solution-chemistry-based studies of the respective components of Pb-BHA complexes in cassiterite flotation (Tian et al, 2017, 2018a,b; Cao et al, 2019) showed that lead ions and their hydroxide ions form Pb(H 2 O) and Pb(OH)(H 2 O) with water and then react with the BHA anion to produce HO-Pb-BHA complexes. He et al (2018a,b) characterized the structure of Pb-BHA complexes in aqueous solutions through theoretical calculations and quantum chemical simulations; the results showed that the Pb-BHA complexes existed mainly in the form of Pb-(BHA) n = 1, 2 at various solution pH values, and first-principles calculations indicated that Pb(BHA) + is the most stable structure. Both studies concluded that the Pb-BHA complexes in the flotation did not consist of a single structure and proposed that Pb-BHA complexes with multiple structures acted simultaneously on the mineral surface.…”
Section: Introductionmentioning
confidence: 99%